2019
DOI: 10.1590/0037-8682-0458-2018
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis mansoni in the northeast region of brazil: temporal modeling of positivity, hospitalization,and mortality rates

Abstract: Introduction: We aimed to analyze trends in Schistosomiasis positivity, mortality, and hospitalization rates in Northeast Brazil. Methods: We conducted an ecological study using data from the Brazilian Schistosomiasis Control Program, and Hospital and Mortality Information Systems. A joinpoint regression model was used for temporal analysis. Results: The positivity(−4.7%;p<0.001) and hospitalization(−17.7%;p<0.001) rates declined globally, while the mortality remained stationary (−0.8%;p>0.05). However, the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
(11 reference statements)
2
11
0
2
Order By: Relevance
“…A proporção de exames positivos para esquistossomose apresentou oscilações durante o período estudado, com média de 8,6%. Em 2011, ano de maior adesão dos municípios, a positividade foi de 8,5%, percentual semelhante à média dos 10 anos e superior à média nordestina no mesmo ano 33 , bem como a de outros estados de alta prevalência da doença, como Alagoas 34 . Embora a positividade não expresse a prevalência da doença, uma vez que os inquéritos coproscópicos não são realizados para este fim e não têm base em amostra representativa da população, a média encontrada é também semelhante à prevalência obtida no inquérito nacional (8,19%) realizado entre 2010 e 2015 11 .…”
Section: Houveunclassified
“…A proporção de exames positivos para esquistossomose apresentou oscilações durante o período estudado, com média de 8,6%. Em 2011, ano de maior adesão dos municípios, a positividade foi de 8,5%, percentual semelhante à média dos 10 anos e superior à média nordestina no mesmo ano 33 , bem como a de outros estados de alta prevalência da doença, como Alagoas 34 . Embora a positividade não expresse a prevalência da doença, uma vez que os inquéritos coproscópicos não são realizados para este fim e não têm base em amostra representativa da população, a média encontrada é também semelhante à prevalência obtida no inquérito nacional (8,19%) realizado entre 2010 e 2015 11 .…”
Section: Houveunclassified
“…This period is characterized by a systematic decrease in technical surveillance and control actions, which probably compromised state programs operationally and may have contributed to the reduced figures in these epidemiological analyses. In this context, the maintenance of focal areas is worrisome and shows the intensity of the endemic disease, particularly in the last five years, requiring an intensification of surveillance, control, and healthcare actions [ 7 , 8 ]. The severe political–institutional and social crisis that the country is currently going through, particularly since 2016, may have contributed to the intensification of schistosomiasis morbidity and mortality in more recent years [ 18 , 19 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim was to control the transmission of the disease and, above all, to reduce the estimated prevalence of cases, as well as the occurrence of deaths in endemic areas [ 6 ]. However, the disease has maintained its endemic character and remains responsible for a significant burden of morbidity and mortality in the country [ 2 , 7 , 8 ]. It is estimated that approximately 1.5 million people live in high-risk areas risk of transmission, with Brazil’s southeast and northeast regions being most affected [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already reported high prevalence rates in municipalities in the endemic area of Alagoas [7,8,9,10], but none have tried to understand the spatial dynamics of the condition in the state. Thus, the areas of highest priority to adopt measures to prevent and control morbidity of the disease remain unknown.…”
Section: Introductionmentioning
confidence: 99%